Pengaruh Motivasi Belajar dan Lingkungan Teman Sebaya terhadap Hasil Belajar Administrasi Transaksi Siswa Kelas XI Jurusan Bidang Daring Pemasaran SMK Negeri 1 Kota Jambi - Sari, Cindy Permata; Rosmiati, Rosmiati; Sari, Nurmala (YASIN, 2025)
Suboptimal student learning outcomes are often influenced by various internal and external factors, such as low learning motivation and an unsupportive peer environment. This study aims to analyze the influence of learning motivation and peer environment on learning outcomes in the subject of Transaction Administration among Grade XI students majoring in Online Marketing at SMK Negeri 1 Kota Jambi. A quantitative approach was employed using the ex-post facto method. Data were collected via an online questionnaire distributed through Google Forms, with a randomly selected sample of 119 students. Data analysis was conducted using descriptive and inferential statistical techniques. The results show that learning motivation has a positive and significant effect on learning outcomes, with a t value of 2.744 and a significance level of 0.007. Similarly, the peer environment also has a positive and significant effect, with a t value of 2.428 and a significance level of 0.017. Simultaneously, both variables significantly influence learning outcomes, as indicated by an F value of 5.370, which exceeds the F table value of 3.07, and a significance level of 0.006, which is below 0.05. These findings demonstrate that enhancing learning motivation and fostering a supportive peer environment can significantly improve student achievement in Transaction Administration. The study underscores the importance of implementing motivational teaching strategies and cultivating a positive social climate within the school environment.